Scrapman and the Incredible Flying Machine - Bear, Carolyn (Oxford Oxford University Press, 2014)
In Scrapman and the Incredible Flying Machine Winston dreams of making a flying machine. There is just one problem. The machine Winston has made won't fly! Can Scrapman help him? TreeTops Fiction contains engaging novels from top authors and illustrators with the variety children need to develop a love of reading!
Include Illustrations
Keywords: Readers (Elementary) -- Robots -- Scrap metals